Pengaruh Kompetensi, Komunikasi Dan Budaya Organisasi Terhadap Peningkatan Kinerja Pegawai Pada Dinas Pemuda Dan Olahraga Provinsi Sulawesi Selatan - Haeranah (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
This research was conducted because of the influence of competence, communication and organizational culture on employee performance in the Youth and Sports Office of South Sulawesi Province. To know and analyze the competence, communication and organizational culture of employee performance in the Youth and Sports Office of South Sulawesi Province and for the benefit of all parties bound in this research is expected to develop knowledge in the field of human resource management, especially regarding competence, communication and organizational culture in employee performance. The data used in this study was primary data that is a response to questionnaires from respondents with data analysis using multiple linear regression with SPSS 23. The sample in this study was 78 employee respondents at the Youth and Sports Office of South Sulawesi Province. The results of this study stated that competence, communication and organizational culture had a positive and significant influence on employee performance of 75.7% and the remaining 24.3% was influenced by other factors not included in the study.